The Ocean barcode atlas: A web service to explore the biodiversity and biogeography of marine organisms. (10th February 2021) - Vernette, Caroline; Henry, Nicolas; Lecubin, Julien; de Vargas, Colomban; Hingamp, Pascal; Lescot, Magali
Abstract: The Ocean Barcode Atlas (OBA) is a user friendly web service designed for biologists who wish to explore the biodiversity and biogeography of marine organisms locked in otherwise difficult to mine planetary scale DNA metabarcode data sets. Using just a web browser, a comprehensive picture of the diversity of a taxon or a barcode sequence is visualized graphically on world maps and interactive charts. Interactive results panels allow dynamic threshold adjustments and the display of diversity results in their environmental context measured at the time of sampling (temperature, oxygen, latitude, etc). Ecological analyses such as alpha and beta‐diversity plots are produced via publication quality vector graphics representations. Currently, the Ocean Barcode Altas is deployed online with the (i) Tara Oceans eukaryotic 18S‐V9 rDNA metabarcodes; (ii) Tara Oceans 16S/18S rRNA mi Tags; and (iii) 16S‐V4 V5 metabarcodes collected during the Malaspina‐2010 expedition. Additional prokaryotic or eukaryotic plankton barcode data sets will be added upon availability, given they provide the required complement of barcodes (including raw reads to compute barcode abundance) associated with their contextual environmental variables. Ocean Barcode Atlas is a freely‐available web service at: http://oba.mio.osupytheas.fr/ocean‐atlas/ .